Productivity, Nutritive Value, and Profitability of Single and Multi-Species Cover Crops in Dryland Environments - Augustine K. Obour; John D. Holman; Logan M. Simon; Yared Assefa (Kansas Agricultural Experiment Station Research Reports, 2025)
Replacing fallow with dual-purpose cover crops (CCs) can increase the profitability of dryland crop rotations in the semi-arid Great Plains. Little research information is available on CC mixtures that optimize productivity and profitability in dryland environments. Field experiments were conducted from 2015 to 2017 at the Kansas State University Hearting Beason (HB) Ranch near Brownell, KS, to quantify forage productivity, nutritive value, and profitability of spring-planted single or mixed species CCs in a winter wheat-grain sorghum-fallow (WSF) crop rotation. The CC treatments were implemented in the fallow phase ahead of winter wheat planting. Treatments were five spring-planted CC treatments: (1) spring oat; (2) spring triticale; (3) oat and triticale mixture (OT, two-species mixture); (3) oat, triticale, and pea (OTP, three-species mixture); and (5) oat, triticale, pea, radish, turnips, and buckwheat (cocktail, six-species mixture), and chemical fallow. Results showed that CC forage accumulation was 33% to 35% greater in sole triticale and OT mixture compared with sole spring oat or cocktail treatments. Multispecies mixtures, cocktail, and OTP had significantly greater available energy, digestibility, and dry matter intake based on measured CP, ADF, NDF, and in vitro dry matter digestibility (IVDMD) compared with single CC species (oat or triticale). Net return was directly proportional to CC forage accumulation. Averaged across years, net return was $40/a greater for the OT treatment compared with the multi-species mixtures. Our results suggest that simple CC mixtures with greater forage accumulation (for example, sole triticale and OT mixture) are better dual-purpose CC alternatives for the semi-arid Great Plains.
Keywords: cover crop; dryland; forage